Beyond the Classroom: The Role of Personal Branding in Teacher Professional Identity Construction - Izi, Arilana Nur; Saputri , Intan Dian; Rini , Diah Eka Sulistia; Fahrudin , F; Izza, Zuhrufa Redina (Universitas Muhammadiyah Surakarta, 2025)
This study examines the strengthening of the professionalism of Islamic Religious Education (PAI) teachers through the formation of personal branding at SMK Tunas Harapan Plupuh Sragen. PAI teachers have a strategic role in instilling moral and spiritual values in students, but challenges in the digital era make strengthening professionalism very important. Personal branding is seen as a strategy to display a teacher's identity that is inspiring and consistent in attitudes, communication, and actions. The research uses a phenomenological qualitative approach by collecting data through in-depth interviews, observations, and documentation. The results of the study show that authentic and consistent personal branding of PAI teachers can strengthen professionalism, increase confidence, and build harmonious relationships with students and the school environment. Supporting factors include support for the school environment, spiritual and leadership competency standards, and the use of social media. Meanwhile, the inhibiting factors are time limitations, lack of training, and understanding of the concept of personal branding. These findings make an important contribution to the development of a contextual and reflective model for PAI teacher professionalism coaching.